Advancements in LASIK CD-ROM techniques for prevention and management of complications - Gimbel, Howard V., 1934-; Penno, Ellen E. Anderson; Slack Incorporated (Thorofare, NJ : Slack, 2001)
Dr. Gimbel performs and thoroughly details the entire scope of LASIK from the standard myopic to the most challenging of complications. This is a series of video segments showing prevention and management of a wide range of LASIK complications. Each clip is narrated by Dr. Gimbel with a focus on techniques to manage difficult complications, and Dr. Penno follows each clip with a summary. Some procedures included: buttonhole, incomplete pass using the automated corneal shaper, shifted flap, loose epithelium, and mirror spots.
Title from disc label
Installation and operating instructions on leaflet, inserted.
System requirements: for IBM PC: Pentium-based PC or above; Windows 95 or later, or Windows NT; 4X CD-ROM; 16 MB of RAM (32 MB preferred); 10 MB of hard disk storage; 1 MB (or higher) SVGA video card; 8-bit Sound Blaster-compatible sound card; for Macintosh: Power PC or above; 16 MB of RAM (32 MB preferred); 10 MB of hard disk storage; MAC OS version 7.1.2. or later.
Keywords: Keratomileusis, Laser In Situ -- adverse effects; Refractive Errors -- surgery; Postoperative Complications -- prevention & control